1994
DOI: 10.1080/01688639408402629
|View full text |Cite
|
Sign up to set email alerts
|

The nature of memory impairments in multiple sclerosis: Acquisition versus retrieval

Abstract: The present study was designed to examine whether verbal memory impairment in multiple sclerosis (MS) is attributable to impaired information acquisition or compromised retrieval. Twenty-three MS and 23 control subjects were administered a 10-item verbal list-learning task. Subjects were trained to a specific criterion on the verbal test in order to assure equal information acquisition. Following a 30-min delay, retrieval and recognition performance was evaluated. MS subjects required significantly more trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
182
3
21

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 266 publications
(231 citation statements)
references
References 19 publications
25
182
3
21
Order By: Relevance
“…As Table 1 illustrates, existing studies are evenly divided between studies that reported null effects (12) and those reporting significant associations (10). Regarding the studies reporting null findings, the majority (10 of 12) were characterized by small sample sizes, suggesting that low statistical power could account for the absence of significant effects (DeLuca et al, 1994;Fischer, 1988;Grafman et al, 1991;Krupp et al, 1994;Millefiorini et al, 1992;Minden & Schiffer, 1990;Moller et al, 1994;Rao et al, 1984Rao et al, , 1989bSchiffer & Caine, 1991). The other study reporting null findings (Good et al, 1992) excluded significantly depressed MS patients from their sample.…”
Section: Cognitive Dysfunctionmentioning
confidence: 99%
“…As Table 1 illustrates, existing studies are evenly divided between studies that reported null effects (12) and those reporting significant associations (10). Regarding the studies reporting null findings, the majority (10 of 12) were characterized by small sample sizes, suggesting that low statistical power could account for the absence of significant effects (DeLuca et al, 1994;Fischer, 1988;Grafman et al, 1991;Krupp et al, 1994;Millefiorini et al, 1992;Minden & Schiffer, 1990;Moller et al, 1994;Rao et al, 1984Rao et al, , 1989bSchiffer & Caine, 1991). The other study reporting null findings (Good et al, 1992) excluded significantly depressed MS patients from their sample.…”
Section: Cognitive Dysfunctionmentioning
confidence: 99%
“…In particular, cognitive dysfunction affects approximately 43% to 70% of individuals with MS. 2 The degree of cognitive impairment varies among individuals, but the most affected domains include information processing speed 2 and learning and memory. [1][2][3][4] To a lesser extent, impairments in executive functioning, attention, and visuospatial abilities have also been reported. 5 Due to the high prevalence of cognitive impairment in individuals with MS, and its potential to detrimentally affect individuals' vocational and personal life, identification of cognitive deficits is of paramount concern.…”
mentioning
confidence: 99%
“…We also found a significant correlation between the delayed improvement and processing speed, measured with the SDMT, the retroactive interference and the primacy recall only in this MS subgroup. Interactions between processing speed and verbal learning have been frequently reported in MS, these patients needing more trials to learn the same amount of information as controls [42][43][44][45][46]57] and the spaced learning trials being a successful method in MS memory rehabilitation [3,32,46]. Here, we can hypothesize that a slower processing speed may explain the memory profile of the improving subgroup.…”
Section: Discussionmentioning
confidence: 72%
“…Some authors are operationalized this deficit as a pathological score for both cued recalls and delayed recognition [28,26], although a storage deficit could also explain this long-term profile. For others, encoding refers either to the first recallT1 [21,[38][39][40][41] which corresponds to the change of information from sensory input into a form that the memory system can store, or to the evolution throughout the first five trials (learning or acquisition), which corresponds to the change resulting from practice [9,16,27,[42][43][44][45][46]. Our individual results point to the existence of both these latter deficits, with encoding deficits being three times more common than learning deficits (58% and 19% of MS patients respectively).…”
Section: Discussionmentioning
confidence: 99%